1985
DOI: 10.1136/bmj.290.6482.1617
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone and the premenstrual syndrome: a double blind crossover trial.

Abstract: complication it might be difficult to conclude which was the most significant risk factor for death. None the less, overall case fatality rate was highest among children with hyponatraemia.The multiple linear regression model showed that deaths associated with hyponatraemia, hyperkalaemia, and hypoglycaemia were significant at the 010 confidence level, but the effect of confounding factors could not be measured.In the logit regression model, which measures the effect of confounding factors, all the variables e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
55
0
3

Year Published

1990
1990
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(58 citation statements)
references
References 13 publications
0
55
0
3
Order By: Relevance
“…These effects were correlated with significant increases in hippocampal levels of the ␣4 subunit of the GABA A receptor, a possible mechanism for the observed neurosteroid withdrawal effects. Use of the pseudopregnant model here may have application for increased emotional lability and altered BDZ response reported for the premenstrual and postpartum periods (Dennerstein et al, 1985;Sundstrom et al, 1997). In addition, increased CNS levels of 3␣,5␣-THP have been noted during periods of chronic stress in male rats (Purdy et al, 1991), suggesting that 3␣,5␣-THP withdrawal may also arise in association with stressful episodes in both sexes.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…These effects were correlated with significant increases in hippocampal levels of the ␣4 subunit of the GABA A receptor, a possible mechanism for the observed neurosteroid withdrawal effects. Use of the pseudopregnant model here may have application for increased emotional lability and altered BDZ response reported for the premenstrual and postpartum periods (Dennerstein et al, 1985;Sundstrom et al, 1997). In addition, increased CNS levels of 3␣,5␣-THP have been noted during periods of chronic stress in male rats (Purdy et al, 1991), suggesting that 3␣,5␣-THP withdrawal may also arise in association with stressful episodes in both sexes.…”
Section: Discussionmentioning
confidence: 78%
“…The use of a pseudopregnancy model here provided several advantages over use of single or multiple injection or chronic implant, as reported earlier: (1) it is a more physiological paradigm than the other procedures, because progesterone is produced by an endogenous, ovarian source; (2) the time course of progesterone exposure, with progesterone elevated from day 4 to 12, is similar to progesterone exposure during the luteal phase of the menstrual cycle (Dennerstein et al, 1985;Rapkin et al, 1997), thus making this a usef ul model for PMS and postpartum conditions; (3) not only are progesterone and 3␣,5␣-THP released, but a number of other steroids are also naturally released by the ovary and corpus luteum, also making this a better in vivo model (Robinson et al, 1981;K im and Greenwald, 1986); (4) release of progesterone under physiological states, such as estrus, pregnancy, and pseudopregnancy is somewhat episodic (Robinson et al, 1981;K im and Greenwald, 1986), a phenomenon that could not easily be replicated by artificial means of administration. The fact that hormone release is episodic in this model may explain why a single withdrawal cycle was effective in the present study in triggering withdrawal properties, whereas in earlier studies, multiple withdrawal cycles were required (Costa et al, 1995;Smith et al, 1998).…”
Section: Discussionmentioning
confidence: 84%
“…Therefore, exogenous neurosteroids also up-regulate ␣4␤␦ receptors and increase tonic inhibition. Discontinuation of administration of a neurosteroid agonist or the parent compound progesterone (i.e., withdrawal) leads to a 3-fold increase in hippocampal ␣4 and ␦ (but no change in ␥2 expression) (Smith et al, 1998;Sundstrom-Poromaa et al, 2002;Gangisetty and Reddy, 2009) and in premenstrual syndrome-like symptoms such as anxiety and increased seizure susceptibility (Dennerstein et al, 1985;Herzog, 2009).…”
Section: B Neurosteroidsmentioning
confidence: 99%
“…During one of the few controlled, double-blind studies, progesterone was shown to improve many symptoms of women suffering from premenstrual syndrome (116), including alleviation of depression. Because progesterone is metabolized to many different neuroactive steroids, it is difficult to determine which hormone(s) ultimately confer the effect.…”
Section: E Neurosteroidsmentioning
confidence: 99%